Balaenoptera acutorostrata Lacepede 1804 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Balaenoptera acutorostrata Lacepede, 1804. Hist. Nat. Cetacees, p. 37, 134. TYPE LOCALITY: France, Cherbourg, Mancha. DISTRIBUTION: Worldwide, subtropical to arctic waters. COMMENT: Includes bonaerensis; see Omura, 1975, Sei. Rep. Whales Res. Inst. (Tokyo), 27:1 -36. MN considered bonaerensis a distinct species. PROTECTED STATUS: CITES - Appendix II as Order Cetacea. ISIS NUMBER: 5301411007001001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 302, DOI: 10.5281/zenodo.7352983